2019
DOI: 10.1109/jphotov.2019.2917787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MACE Parameters on Electrical and Optical Properties of ALD Passivated Black Silicon

Abstract: Metal-assisted chemical etching (MACE) enables efficient texturing of diamond-wire sawn multicrystalline silicon (mc-Si) wafers. However, the excellent optics are often sacrificed by polishing the surface to achieve better surface passivation with chemical-vapor-deposited (CVD) silicon nitride (SiNx). In this work, we show that a polishing step is not required when CVD SiNx is replaced with atomic-layer-deposited (ALD) aluminum oxide (Al2O3). Indeed, while polishing increases reflectance, it has in general onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…Additionally, the thickness has little influence on the reflectivity, but the increase of thickness will increase the stability of the reflectivity. In 2019, K. Chen et al [ 53 ] fabricated black silicon by MACE, and the researchers studied the effect of silver ion concentration on the optical and electrical performances of the material in the etching solution. The results show that the silver ion concentration has an effect on the porosity of black silicon samples, and the lower concentration of silver ion can improve the electrical performance, but has some damage to the optical performance.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the thickness has little influence on the reflectivity, but the increase of thickness will increase the stability of the reflectivity. In 2019, K. Chen et al [ 53 ] fabricated black silicon by MACE, and the researchers studied the effect of silver ion concentration on the optical and electrical performances of the material in the etching solution. The results show that the silver ion concentration has an effect on the porosity of black silicon samples, and the lower concentration of silver ion can improve the electrical performance, but has some damage to the optical performance.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…( d ) Different etching time in high concentration Ag + solution. Adapted from reference [ 53 ], with permission from IEEE © 2020.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…While there might be some concerns about the industrial applicability of the nanostructures, it has been shown that the black-Si nanostructures survive well in the industrial mass production lines [47] and their manufacturing costs can be competitive even in the cost-driven photovoltaics industry [48]. Furthermore, there are also alternative cheaper nanotexturing technologies available, such as metal assisted chemical etching, that can be considered [49,50].…”
mentioning
confidence: 99%
“…2. Details on the mathematical equations of current density of the cathodic process and chemical equations of the two half reactions of the redox couple (reactions at cathode and anode) can be found in related literatures [25][26][27]. From Fig.…”
Section: Resultsmentioning
confidence: 99%